Study on the Aesthetic Tension between the Assumptions Quote and the Authenticity Quote in Theatre Characterization - Liu, Xiaotong; Potiwetchaku , Supavadee; Xu, Yuxiao (Journal of Dhamma for Life, 2025)
This research aims to study 1. To explore the aesthetic tension between the assumptions quot and the Authenticity quot in Theatre Characterisation. 2. To explore the aesthetic phenomenon of the assumptions quot and the Authenticity quot in theatre contributes to the development of theatre art. The research methods include literature survey and interview. The research results illustrate the impact of aesthetic tension on dramatic character creation and actor stage resentation, including in-depth exploration of character connotations, promotion of plot development, and strengthening of theme expression. The research discussion and suggestions section further summarizes and extends the ideas, exploring the aesthetic tension between assumptions and authenticity in the creation of dramatic characters, as well as the aesthetic phenomenon of “assumption” and “authenticity” in drama, which is helpful to the art of drama. development.